AN ANALYSIS ON CHINA’S NATIONAL INTEREST IN AFGHANISTAN DURING THE UNITED STATES MILITARY WITHDRAWAL ERA - Mohd Ali @ Ibrahim, Mohamad Qayyum Afifuddin; Wong , Chooi Ye (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
China has been playing active role in Afghanistan during the post-United States withdrawal from military intervention. The main problem statement laid on China’s national interest in rebuilding Afghanistan from the perspectives of security, economy, and politics. The main objective of this study aims to determine the development of China-Afghanistan bilateral relations and further analyses China’s national interests in Afghanistan in addressing the emerging and existential challenges faced by China in Afghanistan. Multiple qualitative research methods are used in this study involve secondary data collection and thematic analysis approach for reporting. Based on the study, the researchers have found that China’s push on the bilateral ties with Afghanistan in the aftermath of the United States military intervention is complex and diverse. Itis resulted from a confluence of geopolitical, diplomatic, economic, and security factors. China lays the groundwork in Afghanistan plausibly demonstrates a commitment to statecraft that extends beyond short-term goals, as it navigates issues of internal security while also promoting stability in the region and interacting with international society. As the conclusion, by utilizing the neo-realist lenses as the theoretical framework, this paper has found that the emerging discussion carries the potential of mutual prosperity, stability, and a diplomatic tapestry woven with strands of understanding and shared goals as these two nations embark on closer bilateral ties towards a robust future.